IN VITRO COMPARISON OF THE ANTIBACTERIAL ACTIVITY OF ETHANOLIC EXTRACT OF AZADIRACHTA INDICA LEAVES WITH GENTAMYCIN, AMPICILLIN, NITROFURANTOIN, AND COTRIMOXAZOLE ON BACTERIAL PATHOGENS ISOLATED FROM URINARY TRACT INFECTION PATIENTS - Jindal, Meenakshi; S, Chauhan (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Â  Â Objective: In vitro comparison of the antibacterial activity of ethanolic extract of Azadirachta indica (neem) leaves with gentamycin, ampicillin, nitrofurantoin, and cotrimoxazole in bacterial pathogens isolated from urinary tract infection (UTI) patients. Methods: Ethanolic extract of neem leaves was prepared by the standard method. The antimicrobial activity against bacteria isolated from UTI patients was determined by agar well diffusion method and then mean zone of inhibition of neem extract was compared with a mean zone of inhibition of gentamycin, ampicillin, nitrofurantoin, and cotrimoxazole. Results: Among 200 samples which were included in the study, bacteria isolated were Escherichia coli (60%), Klebsiella pneumoniae (15%), Pseudomonas aeruginosa (11%), Enterococcus faecalis (5%), Proteus mirabilis (3%), and Staphylococcus aureus (6%). The result obtained was statistically analyzed by unpaired t-test. The difference in the mean diameter of the zone of inhibition between ethanolic extract of Azadirachta indica (neem) leaves and nitrofurantoin was statistically highly significant for K. pneumoniae (p<0.0001) and P. mirabilis (p=0.01) and insignificant for other bacteria. On comparing, the mean diameter of the zone of inhibition of ethanolic extract of A. indica (neem) leaves with ampicillin and cotrimoxazole, it was found to be statistically highly significant for all bacteria E. coli (p<0.0001), K. pneumoniae (p<0.0001), P. aeruginosa (p<0.0001) E. faecalis (p<0.001), and S. aureus (p<0.0001) expect P. mirabilis. The mean diameter of the zone of inhibition of ethanolic extract of A. indica (neem) leaves when compared with gentamycin was statistically highly significant for all the bacteria. Conclusion: The ethanolic extract of A. indica leaves has antibacterial activity. Antibacterial activity of ethanolic extract of A. indica leaves is comparable to nitrofurantoin for bacteria E. coli, P. aeruginosa, E. faecalis, and S. aureus. Ethanolic extract of A. indica leaves has similar antibacterial activity as ampicillin and cotrimoxazole for bacteria P. mirabilis. The antibacterial activity of gentamycin is less as compared to an ethanolic extract of A. indica leaves for all the bacteria.